Religious Moderation in Early Childhood Education: Integration, Implementation, and Challenges within the Merdeka Curriculum - Nur Lailatul Fitri; Ahmad Suyanto (Universitas Al-Hikmah Indonesia, 2025)
This study aims to examine 1) the integration of religious moderation values into the Merdeka Curriculum at RA Muslimat Al Hidayah, 2) the implementation of these values in the learning process at RA Muslimat Al Hidayah, and 3) the challenges faced by teachers in applying religious moderation at RA Muslimat Al Hidayah.This research employs a qualitative descriptive method and was conducted at RA Muslimat Al-Hidayah in Gesikharjo, Tuban. The informants in this study consisted of four classroom teachers and the school principal. Data collection techniques included observation, structured interviews, and document analysis. The data were analyzed using the Miles and Huberman model.The findings of this study are as follows, 1) Religious moderation values can be integrated into various components of the Early Childhood Education (ECE) curriculum within the implementation of the Merdeka Curriculum.2)The application of religious moderation values in the ECE curriculum is carried out through both intracurricular activities and the implementation of student character development projects at the early childhood level. 3) One of the main challenges faced by teachers is the limited understanding of the concept of religious moderation among educators.